Alud de datos - Bernal, Isabel (Anuario ThinkEPI, 2015)
Reseña del informe:Mossink,Wilma;Â  Bijsterbosch, Magchiel;Â  Nortier, Joeri (2013). European landscape study of research data management. Utrecht: SURF.http://goo.gl/CJNlTX